Collaboration, dialogue and expansive learning: the use of paired and multiple placements in the school practicum - Sorensen, Peter (Elsevier, 2014)
This study examines the way in which paired or multiple placements of student teachers in the school practicum can support learning through the promotion of collaboration and dialogue. It draws on data collected across six higher education institution (HEI)-secondary schools partnerships in England and focuses on a series of 20 case studies from one partnership. The results suggest that peer placements can support more expansive and deeper learning, especially where attention has been given to the structuring of the placements and the role of the mentor or cooperating teacher. In such cases there are also reciprocal benefits for the school.